Synthesis of hexaphyrins and N-fused pentaphyrins bearing pyridin-4-ylsulfanyl groups - Figueira, Flavio
In recent years much attention has been devoted to expanded macrocyclic chemistry. Nevertheless, while several advancements were achieved in the synthesis of novel expanded porphyrin architectures, not much has been developed in the functionalization of these macrocycles. This report shows the selective replacement of the p-fluorine atoms of meso-pentakis(pentafluorophenyl) N-fused [22]pentaphyrin and meso-hexakis(pentafluorophenyl) [26]hexaphyrin with 4-mercaptopyridine moieties, thus increasing their potential as ligands for coordination chemistry and catalysis or electronic transfer applications striving new synthetic methodologies and a new set of specific applications for this type of compounds.